Antibiotic-resistant characteristics and horizontal gene transfer ability analysis of extended-spectrum β-lactamase-producing Escherichia coli isolated from giant pandas - Liu, Haifeng; Fan, Siping; Zhang, Xiaoli; Yuan, Yu; Zhong, Wenhao; Wang, Liqin; Wang, Chengdong; Zhou, Ziyao; Zhang, Shaqiu; Geng, Yi; Peng, Guangneng; Wang, Ya; et al. (Frontiers in Veterinary Science, 2024)
Extended-spectrum β-lactamase (ESBL)-producing Escherichia coli (ESBL-EC) is regarded as one of the most important priority pathogens within the One Health interface. However, few studies have investigated the occurrence of ESBL-EC in giant pandas, along with their antibiotic-resistant characteristics and horizontal gene transfer abilities. In this study, we successfully identified 12 ESBL-EC strains (8.33 %, 12/144) out of 144 E. coli strains which isolated from giant pandas. We further detected antibiotic resistance genes (ARGs), virulence-associated genes (VAGs) and mobile genetic elements (MGEs) among the 12 ESBL-EC strains, and the results showed that 13 ARGs and 11 VAGs were detected, of which blaCTX-M (100.00 %, 12/12, with 5 variants observed) and papA (83.33 %, 10/12) were the most prevalent, respectively. And ISEcp1 (66.67 %, 8/12) and IS26 (66.67 %, 8/12) were the predominant MGEs. Furthermore, horizontal gene transfer ability analysis of the 12 ESBL-EC showed that all blaCTX-M genes could be transferred by conjugative plasmids, indicating high horizontal gene transfer ability. In addition, ARGs of rmtB and sul2, VAGs of papA, fimC and ompT, MGEs of ISEcp1 and IS26 were all found to be co-transferred with blaCTX-M. Phylogenetic analysis clustered these ESBL-EC strains into group B2 (75.00 %, 9/12), D (16.67 %, 2/12), and B1 (8.33 %, 1/12), and 10 sequence types (STs) were identified among 12 ESBL-EC (including ST48, ST127, ST206, ST354, ST648, ST1706, and four new STs). Our present study showed that ESBL-EC strains from captive giant pandas are reservoirs of ARGs, VAGs and MGEs that can co-transfer with blaCTX- M via plasmids. Transmissible ESBL-EC strains with high diversity of resistance and virulence elements are a potential threat to humans, animals and surrounding environment.